Is titanium-zirconium alloy a better alternative to pure titanium for oral implant? Composition, mechanical properties, and microstructure analysis - Ajay Sharma; John N. Waddell; Kai C. Li; Lavanya A Sharma; David J. Prior; Warwick J. Duncan (Elsevier, 2021)
Introduction: Titanium (Ti) is widely accepted as a biomaterial for orthopaedic and dental implants, primarily due to its capacity to integrate directly into the bone and its superior corrosion resistance. It has been suggested that titanium-zirconium alloy (TiZr), with 13-17% of zirconium, has better mechanical properties than pure Ti, but there are very few published studies assessing the suitability of TiZr for high-load- bearing implants. This study aimed to compare the mechanical properties and microstructures of TiZr and commercially pure titanium (Ti). Methodology: Pure Ti and TiZr alloy discs were prepared and subjected to characterisation by nanoindentation, electron dispersive spectroscopy (EDS), X-ray diffraction (XRD), and electron backscatter diffraction (EBSD). Results: The TiZr alloy was found to have significantly lower elastic modulus value (p < 0.0001) and greater hardness than Ti (p < 0.05). The EDS results confirmed the presence of Zr (13-17%) in the TiZr alloy, with XRD and EBSD images showing microstructure with the alpha phase similar to commercially available Ti. Conclusion: The lower elastic modulus, higher hardness, presence of alpha phase, and the finer grain size of the TiZr alloy make it more suitable for high-load-bearing implants compared to commercially available Ti and is likely to encourage a positive biological response.